Retention, Release and transformation of Phosphate and Potash in Relation to Soil Fertility Potential of Three Major Soils - Kulkarni, D.R. (Asian Journal of Chemistry, 2010)
Present work reports behaviour of phosphate and potash fertilizer in three distinct soils. The quantity adsorbed, desorbed and transformed is calculated to interpret fertility potentials of these soils. Bounding energy of the soils to the nutrients is computed from Langmuir's adsorption isotherms, desorption and distribution patterns are developed from the quantities extracted in different forms.